Coherence of Sports Clubs Development and Consumer Needs: Aspect of Research Interests (Laisvalaikio tyrimai, 2013)
One of the main preconditions of successful coherence between the development of sports clubs and consumer needs is the satisfaction of consumers’ needs and expectations by improving the quality of services. Quality of services develops customer loyalty, ensures the attraction of potential users, employee satisfaction, and the formation of a positive image in the market. On the basis of research results, the paper presents coherence factors of sports clubs development and consumer needs. It discusses to what extent this determines the peculiarities of activities. It is considered that one of the most important factors stimulating the development of sports clubs and organizations, competing with each other, maintaining or helping to conquer the markets, is the satisfaction of consumer needs. However, the needs of consumers of sports clubs are usually analysed through the dimensions of quality (Bodet, 2006). Quality creates the image of the sports clubs, and it has a direct impact on business productivity, profit growth and consumers’ satisfaction. Research methods applied were the analysis of scientific literature, systemization and generalization. The research approach was qualitative. Content analysis was applied. The research emphasis was on the demand of sports clubs services, loyalty to the club, consumers’ needs and motivation. The development of sports clubs is the consumer’s perceived utility, which is created by the service providers’ attempts, using a variety of communication efforts and promotion means. All services at sports clubs can be classified into three groups: 1) basic services, 2) additional peripheral services, and 3) supporting services, known as special and recreational services. Furthermore, research on the market should be further continued in order to better understand the expectations of consumers and to meet their needs.Keywords: sports club, service, satisfaction, image, motivation.